AN ALTERNATIVE DIAGNOSTIC DESIGN FOR CHRONIC KIDNEY DISEASE DETECTION BASED ON CYSTATIN C - Stephen, Bjorn John; Desai, Dignya; Datta, Manali (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: Chronic Kidney Disease (CKD) is usually diagnosed by measuring the glomerular filtration rate (GFR) and diagnostics are still inadequate at the clinical level. Most of the diagnostic kits available estimate GFR rate by determining clearance of serum creatinine using various instrumentation generally available at hospitals. Serum creatinine is considered the major marker for renal deficiency disorders. Additionally, it is also an indicator of muscle mass and dietary intake. Hence, the need for a more reliable marker for CKD arises. A low molecular weight protein cystatin C has been found to be a reliable biomarker for detection of kidney function as it is solely filtered by the glomerulus and not secreted by renal tubules. Method: The basic set up of the kit was designed using a syringe containing multi walled carbon nanotube (MWCNT) conjugated protease. Casein beads were immersed inÂ  PBS buffer in the syringe. The Glass/MWCNT/papain solid support was subsequently inserted into the syringe in such a way, that the beads came in contact with the immobilized enzyme conjugate. The inhibitory action of cystatin C against protease forms the basis for the functioning of the kit Results: Results indicated that papain while immobilization needs to be in dynamic conformation. At 37 C gave better activity as compared to protein immobilized at 4C. FTIR observations confirmed the physical adsorption on the MWCNTs. The experimentation confirmed the feasibility of using prototype for detection of cystatin C. Discussion: Papain conjugated with MWCNT indicated its temperature and pH stability. The initial design of the diagnostic kit for the detection of CKD has shown to be successful with a good detection range corresponding to stage I and II of CKD. Further testing needs to be done for the prototype using patient samples. Keywords: Chronic kidney disease, Diagnostic kit, Immobilized papain, Protease inhibitor.Â 